2011
DOI: 10.1007/s10517-011-1321-0
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Blood-Stimulating Effect of Immobilized Granulocyte Colony-Stimulating Factor by Immobilized Hyaluronidase

Abstract: We evaluated whether immobilized hyaluronidase can modify the hematotropic effect of immobilized granulocyte CSF (G-CSF). The preparation of immobilized hyaluronidase (50 arb. units per mouse) potentiated the specific effect of immobilized G-CSF on granulomonocytopoiesis. The preparation was shown to facilitate the indirect effect of immobilized G-CSF on hemopoiesis (stimulation of the erythroid and lymphoid hemopoietic stems). These changes were accompanied by an increase in functional activity of hemopoietic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…Experimental studies demonstrated potentiation of the specifi c effects of some bioactive substances by immobilized hyaluronate-endo-β-N-acetylhexosaminidase (imHEA-HA), an hyaluronidase analogue playing the key role in HA metabolism [2,4]. This drug created by electron-beam synthesis nanotechnology is a virtually nontoxic compound with manifest systemic effects (in contrast to unmodifi ed enzyme), also effective in oral treatment [7,8,10], which is explained by its resistance to serum and tissue degradation factors [13,14] and proteolytic enzymes of the gastrointestinal tract [6,7].…”
mentioning
confidence: 99%
“…Experimental studies demonstrated potentiation of the specifi c effects of some bioactive substances by immobilized hyaluronate-endo-β-N-acetylhexosaminidase (imHEA-HA), an hyaluronidase analogue playing the key role in HA metabolism [2,4]. This drug created by electron-beam synthesis nanotechnology is a virtually nontoxic compound with manifest systemic effects (in contrast to unmodifi ed enzyme), also effective in oral treatment [7,8,10], which is explained by its resistance to serum and tissue degradation factors [13,14] and proteolytic enzymes of the gastrointestinal tract [6,7].…”
mentioning
confidence: 99%